2020
DOI: 10.1097/meg.0000000000001520
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-4, aspartate transaminase-to-platelet ratio index, and gamma-glutamyl transpeptidase-to-platelet ratio for risk assessment of hepatocellular carcinoma in chronic hepatitis B patients: comparison with liver biopsy

Abstract: Background and aims: It is well known that hepatocellular carcinoma (HCC) develops as a consequence of hepatic fibrosis progression. Thus, early identification of advanced liver fibrosis is very important. This study evaluated the prognostic value of FIB-4, the aspartate transaminase to-platelet ratio index (APRI), and the gamma-glutamyl transpeptidase-toplatelet ratio (GPR) for predicting HCC development using histological fibrosis stage as a reference in Asian chronic hepatitis B (CHB) patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Similar to GGT, AKP is also a marker of liver fibrosis as part of the liver biochemical testing routine. As previously reported, non-invasive indices APRI, FIB-4 and GPR can be calculated using age, ALT, AST, GGT and PLT, all of which can be applied to predict fibrosis in patients with CHB (28). For this reason, it was hypothesized that the APPR may also be an useful index for distinguishing liver fibrosis from CHB.…”
Section: P-valuesmentioning
confidence: 95%
“…Similar to GGT, AKP is also a marker of liver fibrosis as part of the liver biochemical testing routine. As previously reported, non-invasive indices APRI, FIB-4 and GPR can be calculated using age, ALT, AST, GGT and PLT, all of which can be applied to predict fibrosis in patients with CHB (28). For this reason, it was hypothesized that the APPR may also be an useful index for distinguishing liver fibrosis from CHB.…”
Section: P-valuesmentioning
confidence: 95%
“…The aminotransferase-to-platelet ratio index (APRI, Equation ( 1)) and fibrosis-4 (FIB-4, Equation ( 2)) index are popular noninvasive indices to predict liver fibrosis in chronic viral hepatitis [12][13][14]. Furthermore, baseline FIB-4 has a higher predictive performance for HCC than other indices in patients with CHB [15][16][17]. An Asian study reported that patients with noncirrhotic CHB receiving long-term NA therapy who had a FIB-4 < 1.29 at baseline had the lowest risk for HCC [18].…”
Section: Introductionmentioning
confidence: 99%
“… 24 FIB‐4 seems to be more useful than GPR and APRI in predicting the risk assessment of CHB‐induced HCC development. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Dong et al suggested that HBeAg status should be taken into account when GPR was used to diagnose liver fibrosis and cirrhosis 24 . FIB‐4 seems to be more useful than GPR and APRI in predicting the risk assessment of CHB‐induced HCC development 29 …”
Section: Discussionmentioning
confidence: 99%